Expanding its universe. (Economist, 2007)
This article reports on the comeback of Sun Microsystems; the computer-maker had suffered several years of falling sales but is now growing again. CEO Jonathan Schwartz is engaging in a vigorous plan to grow in an industry that is supposedly stagnant. Sun has made its operating system, Solaris, open-source allowing everyone access without charge.